Co-Administration of High-Dose Nebulized Colistin for Acinetobacter baumannii Bacteremic Ventilator-Associated Pneumonia: Impact on Outcomes - Ioannis Andrianopoulos; Nikolaos Kazakos; Nikolaos Lagos; Theodora Maniatopoulou; Athanasios Papathanasiou; Georgios Papathanakos; Despoina Koulenti; Eleni Toli; Konstantina Gartzonika; Vasilios Koulouras (MDPI AG, 2024)
Acinetobacter baumannii (A. baumannii) is a difficult-to-treat (DTR) pathogen that causes ventilator-associated pneumonia (VAP) associated with high mortality. To improve the outcome of DTR A. Baumannii VAP, nebulized colistin (NC) was introduced with promising but conflicting results on mortality in earlier studies. Currently, NC is used at a much higher daily dose compared to the past. Nevertheless, there is little evidence on the effect of high-dose NC on the outcomes of A. baumannii VAPs, especially in the current era where the percentage of colistin-resistant A. baumannii strains is rising. We conducted a retrospective study comparing bacteremic A. baumannii VAP patients who were treated with and without NC co-administration and were admitted in the Intensive Care Unit of University Hospital of Ioannina from March 2020 to August 2023. Overall, 59 patients (21 and 38 with and without NC coadministration, respectively) were included. Both 28-day and 7-day mortalities were significantly lower in the patient group treated with NC (52.4% vs. 78.9%, p 0.034 and 9.5% vs. 47.4%, p 0.003, respectively). Patients treated with NC had a higher percentage of sepsis resolution by day 7 (38.1% vs. 13.5%, p 0.023) and were more likely to be off vasopressors by day 7 (28.6% vs. 8.1%, p 0.039). The addition of NC in the treatment regime of A. baumannii VAP decreased mortality.